2008
DOI: 10.2172/947483
|View full text |Cite
|
Sign up to set email alerts
|

Wide-Area Energy Storage and Management system to Balance Intermittent Resources in the Bonneville Power Administration and California ISO Control Areas

Abstract: The entire project addresses the issue of mitigating additional intermittency and fast ramps that occur at higher penetration of intermittent resources, including wind generation, in the Bonneville Power Administration (BPA) and the California Independent System Operator (California ISO) control areas. The proposed Wide Area Energy Storage and Management System (WAEMS) will address the additional regulation requirement through the energy exchange between the participating control areas and through the use of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 3 publications
0
67
0
1
Order By: Relevance
“…Walawalker a nd A pt indicated that efficiency of the NaS battery was 75% [8] [8]. In our sensitivity study, efficiency was analyzed at 90%, as indicated in Phase I report by Makarov et al [6].…”
Section: Assumptionsmentioning
confidence: 87%
See 1 more Smart Citation
“…Walawalker a nd A pt indicated that efficiency of the NaS battery was 75% [8] [8]. In our sensitivity study, efficiency was analyzed at 90%, as indicated in Phase I report by Makarov et al [6].…”
Section: Assumptionsmentioning
confidence: 87%
“…The algorithm used to generate regulation and real-time dispatch signals was developed in previous research. For detailed information, please refer to [5] and [6].…”
Section: Modeling Approachmentioning
confidence: 99%
“…Technically, the proposal here exposed has developed a lot of points to defend it but, it is necessary to complement it with economic arguments. During the last years an important work to sustain the renewable option in regulated or free markets has been presented by many authors (Makarov et al 2009). One basic analysis, introduced in (García & Linare,2006), compares the current electric system costs with respect to one only based on renewable energy, where important aspects are revealed that strongly support.…”
Section: Future Research Linesmentioning
confidence: 99%
“…Phase I and other California Energy Commission studies [1]- [6] have shown that fast-ramping balancing services could potentially reduce the regulation and load-following requirement by up to 30%. Therefore, it is important for BPA and CAISO to seek additional fast load-following and regulation resources to meet challenges of the high penetration of wind in BPA and CAISO balancing authorities.…”
Section: Technical Needsmentioning
confidence: 99%
“…The net present value (NPV) 4 Two payment methods were studied for the regulation service: pay-by-capacity and pay-byenergy.…”
Section: Battery Storage Evaluationmentioning
confidence: 99%